2019
DOI: 10.1039/c8ob03178a
|View full text |Cite
|
Sign up to set email alerts
|

Allylic azides: synthesis, reactivity, and the Winstein rearrangement

Abstract: Allylic azides are useful synthetic intermediates, the Winstein rearrangement complicates usage, and mechanistic knowledge can enable selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 227 publications
(326 reference statements)
0
44
0
1
Order By: Relevance
“…in pyridine (20 mL) was added for acetylating. Recrystallization with ethanol was done to produce NMR pure white crystal of compound [3] in very good yield (Carlson and Topczewski, 2019;Kantaria et al, 2018;Hajipour and Ghorbani, 1920;Costa et al, 2017).…”
Section: Azidationmentioning
confidence: 99%
“…in pyridine (20 mL) was added for acetylating. Recrystallization with ethanol was done to produce NMR pure white crystal of compound [3] in very good yield (Carlson and Topczewski, 2019;Kantaria et al, 2018;Hajipour and Ghorbani, 1920;Costa et al, 2017).…”
Section: Azidationmentioning
confidence: 99%
“…The efficient synthesis of nagelamide alkaloids (a subfamily of oroidin natural products derived from marine sponges) has garnered interest (Du et al, 2006;Das et al, 2016) since first reported (Endo et al, 2004). Allylic azides (Carlson & Topczewski, 2019) are fairly reactive making them attractive starting compounds to convert into amides. Our group has successfully synthesized a number of azide-containing imidazole derivatives and determined their structures.…”
Section: Chemical Contextmentioning
confidence: 99%
“…[7][8][9][10] Allylic azides are building blocks for the synthesis of natural products and nitrogen-containing heterocycles of pharmacological relevance. [11][12][13][14] Despite the importance of these useful synthons, their applicability in synthetic schemes has been difficult due to their existence as a regioisomeric mixture that interconverts rapidly at room temperature, being in general inseparable (Figure 1). 15,16 The allylic azide rearrangement was first reported by Gagneux, Winstein, and Young in 1960 (known as Winstein's rearrangement).…”
Section: Examples Of Those Reactions Include Classical Name Reactionsmentioning
confidence: 99%